Literasi Keberagamaan Masyarakat Daerah 3T Di Kabupaten Pesisir Barat Serta Relevansinya Dengan Sikap Toleransi Terhadap Penganut Agama Minoritas - Yetri, Yetri; Iqbal, Agung M; Amaliah, Eni (AL-ADYAN, 2019)
Advanced society is characterized by a literate society that has a high civilization. Literacy is the most important reference about the pros and cons of a society in the future. Religious literacy, is the ability to see and analyze the meeting point between religion and social, political and cultural life. The importance of religious literacy in the midst of a pluralistic society is also related to the increasingly intolerant attitudes among religious adherents. Religion is currently very easy to be used as issues that can trigger divisions in the community. Pesisir Barat Regency in Lampung Province, is one of the 3T areas, has quite a variety of religious adherents, and Islam is the major religion with the highest number of adherents. However, the data shows that up to now there has never been a serious conflict or conflict between religious followers in this area. Research with this qualitative approach is intended to describe the level of religious literacy in the two 3T regions, its relevance to the attitude of tolerance towards adherents of minority religions. The results showed that, there are five dimensions that can be used as benchmarks to see someone's religious level, namely the dimensions: beliefs, religious practice experience, religious knowledge, and practice dimensions. In general, the diversity of the West Coast community is very good. In addition, there is a relevance or suitability of the relationship between the level of religious literacy in the West Pesisir district people with an attitude of tolerance